Personal growth initiative as a predictor of psychological distress in college students during the covid-19 pandemic - Fathiyah, Amya Bunga; Mardhiyah, Sayang Ajeng (Jurnal Ilmiah Psikologi Terapan, 2023)
This study aims to determine the role of personal growth initiatives (PGI) in psychological distress among undergraduate students during the COVID-19 pandemic. This study hypothesizes that there is a role of PGI in psychological distress among undergraduate students during the COVID-19 pandemic. Respondents in this study were 200 active undergraduate students in Indonesia. The sampling technique used was purposive sampling. The measuring instruments were the General Health Questionnaire-12 (GHQ-12) and the PGI scale. The results show that PGI had a significant role in psychological distress, with F(1.198) = 13.784, p= 0.000, R2 = 0.065, and R2 adjusted = 0.060. The regression coefficient (β = -0.175) indicated that an increase in PGI, on average, could decrease the psychological distress score by 0.175. Thus, the hypothesis proposed in this study can be accepted.